Implementation of a nurse-driven protocol for indwelling urinary catheter removal and novel utilization dashboard: a pre/postintervention observational study - Michelle Kamel; Nichole Harris; Andrew Berry; Theodore Warsavage; Mary T. Bessesen; Shelley E. Kon (Therapeutic Advances in Infectious Disease)
Background: Nurse-driven protocols (NDPs) for urinary catheter removal are proven tools for decreasing catheter-associated urinary tract infections (CAUTIs); however, they are not used consistently in acute care settings. Objective: To determine the impact of a NDP for urinary catheter removal on CAUTI rates and device utilization ratio. Design: Pre/postintervention, observational study at a 160-bed, level 1a academically affiliated Veterans Affairs (VA) hospital. Methods: CAUTI rates and device utilization ratios were examined before and after implementation of the NDP. Results: The CAUTI rate decreased from 0.99 per 1,000 urinary catheter days in the preintervention period to 0.27 per 1000 urinary catheter days in the postintervention period. The device utilization ratio (catheter days/patient days) decreased from 14% in the preintervention period to 12% in the postintervention period. Conclusion: The NDP reduced the CAUTI rate and the device utilization ratio. A multidisciplinary project team and use of a data visualization dashboard may be valuable implementation strategies to increase utilization of NDPs such as HOUDINI.